TOKSISITAS AKUT IN VITRO EKSTRAK DAUN JOMBANG(Taraxacum officinale F.H. Wigg) DENGAN METODEBRINE SHRIMP LETHALITY TEST (BSLT) - Dian Mega Sugiyarto, (2023)
Toxicity is the characteristic of a substance that can cause harmful effects. This study aims to determine the toxicity of dandelion leaves (Taraxacum officinale F.H. Wigg) to Artemia salina Leach larvae within 24 hours. Toxicity is measured using the Brine Shrimp Lethality Test (BSLT) method and the LC50 value. In addition to toxicity, this study also carried out phytochemical screening. Dandelion leaves were extracted using the maceration method with 96% and 50% ethanol solvents. The results showed that dandelion leaves contain alkaloids, flavonoids, steroids/triterpenoids, and phenols. Toxicity testing used dilution series of 50 ppm, 100 ppm, 200 ppm, and 400 ppm. The test results obtained LC50 values of 121,477 ppm in 96% ethanol and LC50 values of 165,223 ppm in 50% ethanol (Toxic).